Composite membrane for lithium battery and preparation method of composite membrane

By co-mixing aromatic polyamide and polyacrylonitrile and passing through liquid solvent bath, stretching and UV optical radiation treatment, a composite film with high tensile performance and excellent electrical performance was prepared, which solved the problem of insufficient thermal stability and porosity of the existing lithium battery separator, and significantly improved the circulation performance and safety of the lithium battery.

CN119725989APending Publication Date: 2025-03-28ZHEJIANG GOLDEN FEATHER NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411893825.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing lithium battery separators have low thermal stability and porosity, and the tensile performance of aromatic polyamide films is poor, prone to fracture, affecting production efficiency and membrane characteristics.

Method used

The composite film of aromatic polyamide and polyacrylonitrile is prepared by co-mixing, liquid solvent bath, stretching treatment and UV optical radiation cyclization cross-linking to improve its tensile and electrical properties.

Benefits of technology

The tensile performance, thermal stability and electrical performance of the composite film are significantly improved, the amount of electrolyte added of lithium battery is reduced, and the circulation performance and safety of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725989A_ABST
    Figure CN119725989A_ABST
Patent Text Reader

Abstract

The invention provides a composite membrane for a lithium battery and a preparation method of the composite membrane, the composite membrane comprises the following raw materials: aromatic polyamide and polyacrylonitrile, the mass of the polyacrylonitrile does not exceed that of the aromatic polyamide, the linear thermal shrinkage rate of the composite membrane is 0-2%, the elongation rate is 150-350%, the tensile strength is 65-160 Mpa, and the liquid absorption rate is 150-200%. The preparation method comprises the following steps: S1, uniformly mixing aromatic polyamide slurry and polyacrylonitrile slurry to obtain mixed polymer slurry; s2, discharging the mixed polymer slurry into a liquid solvent in a film shape, and performing stretching and other treatment to obtain a base film; s3, the base film is subjected to UV light radiation cyclization crosslinking treatment; and S4, rolling to obtain the composite film. By using the composite membrane for the lithium battery, provided by the invention, the tensile strength and elongation of the composite membrane can be improved, the heat resistance of the composite membrane is improved, the ionic conductivity is improved, the use amount of electrolyte is effectively reduced, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation technology of a composite film for lithium batteries, in particular to a preparation technology of an aromatic polyamide composite film for lithium batteries. Background Art

[0002] Lithium batteries are highly efficient, rechargeable batteries with advantages such as high energy density, no memory effect, low self-discharge and environmental protection. They are widely used in electronic equipment, electric vehicles and other fields. Lithium batteries use lithium ions as charge carriers. During the charging and discharging process, lithium ions move between the positive and negative electrodes to store and release electrical energy.

[0003] Lithium battery separator is one of the key components in the structure of lithium battery. The mechanical and electrical properties of the separator have a great influence on the capacity, cycle performance, safety, etc. of the battery. In the related technology, the separator made of common PE / PP film has poor thermal stability and low porosity. The heat resistance of the body is usually around 130°C. After the separator is coated, it usually has a temperature resistance of around 150°C and a low porosity (32%-45%). Aramid fiber, the full name of which is "polyphenylene phthalate", is a synthetic aromatic polyamide. It is a synthetic linear polymer composed of aromatic rings (Ar-CONH-Ar) connected by amide bonds. It has high temperature resistance and a glass transition temperature above 300°C. The non-solvent induced phase separation method can be used to produce a base film with a high porosity of 50%-80%. Recently, it has received increasing attention in the field of battery separator manufacturing. In the related art, aromatic polyamide membranes are used to improve the thermal stability and porosity of the separator, but the aromatic polyamide-based membrane has poor tensile properties and is easy to break during the production process, thereby affecting the production efficiency and membrane properties. Therefore, there is an urgent need to study a method for preparing an aromatic polyamide composite membrane for lithium batteries in the art, wherein the composite membrane has higher tensile properties and still has excellent electrical properties when used as a battery separator. Summary of the invention

[0004] The present invention provides a composite membrane for lithium batteries and a preparation method thereof. The composite membrane provided by the present invention has excellent tensile properties. The battery separator made of the composite membrane can effectively reduce the amount of lithium battery electrolyte added and significantly improve the cycle performance of lithium ion batteries; and the battery separator made of the composite membrane provided by the present invention has higher wettability, higher ion conductivity, higher charge and discharge rate than traditional separators, and is more resistant to high temperatures, thereby having higher safety. The preparation method provided by the present invention is used to prepare the composite membrane for lithium batteries.

[0005] In view of the limitations of the above-mentioned related technologies, the present invention proposes a composite membrane for lithium batteries and a preparation method thereof.

[0006] The first invention point of the present invention is to provide a composite membrane for lithium batteries. The raw materials for preparing the composite membrane include aromatic polyamide and polyacrylonitrile. The mass of the polyacrylonitrile does not exceed the mass of the aromatic polyamide. Preferably, the mass ratio of the aromatic polyamide to the polyacrylonitrile is: (1-20):1.

[0007] Furthermore, the aromatic polyamide is poly(p-phenylene terephthalamide), poly(m-phenylene isophthalamide), heterocyclic aromatic polyamide containing heteroatoms or fully aromatic polyamide of ortho-aramid, and has a molecular weight of 9W-35W.

[0008] Furthermore, the molecular weight of the polyacrylonitrile is 30W-50W.

[0009] Furthermore, the composite film meets at least one of the following four parameters, and preferably meets the following four parameters at the same time: linear heat shrinkage: 0-2% in both MD and TD directions at 250°C / h; elongation: 150%-350% in both MD and TD directions; tensile strength: 65Mpa~160Mpa in both MD and TD directions, preferably, the tensile strength in the MD direction is higher than the tensile strength in the TD direction; liquid absorption rate: 150%~200%.

[0010] Furthermore, the composite membrane is made by mixing aromatic polyamide and polyacrylonitrile.

[0011] Furthermore, the composite membrane formed after the two raw materials react is a structure in which polyacrylonitrile is partially cyclized and cross-linked, and the polyacrylonitrile and the aromatic polyamide are combined through hydrogen bonds to form an overall structure that is entangled with each other.

[0012] Furthermore, after the two raw materials are mixed together, the mixture is subjected to a liquid solvent bath and / or a stretching treatment. If both treatment methods are used at the same time, the liquid solvent bath is performed first, and then the stretching treatment is performed;

[0013] Furthermore, the aromatic polyamide and polyacrylonitrile are treated by UV light radiation, preferably after the liquid solvent bath, the product treated by the liquid solvent is treated by UV light radiation on both sides. The UV light radiation treatment causes the polyacrylonitrile in the composite film to be partially cyclized and cross-linked, and the positively charged amide groups of the aromatic polyamide are attracted to each other, thereby forming a chain-shaped entangled structure.

[0014] Furthermore, before the two raw materials are blended, solvents are added separately to prepare aromatic polyamide slurry and polyacrylonitrile slurry; preferably, the solid content of the aromatic polyamide slurry is 15%-30%; the solid content of the polyacrylonitrile slurry is 15%-25%; more preferably, the solid content of the mixed polymer slurry is 15%-25%.

[0015] Furthermore, the liquid solvent is a mixed solvent of an organic solvent and water; the organic solvent here is preferably consistent with the solvent used to prepare the slurry.

[0016] Another invention of the present application is to provide a method for preparing a composite membrane for a lithium battery, comprising the following steps:

[0017] S1: slurry preparation: dissolving aromatic polyamide in a first solvent to obtain aromatic polyamide slurry, dissolving polyacrylonitrile in a second solvent to obtain polyacrylonitrile slurry, and mixing the two evenly to obtain a mixed polymer slurry;

[0018] S2: Film making: the mixed polymer slurry is extruded and passed through a liquid solvent bath, stretched, cleaned, and dried to obtain a base film.

[0019] S3: base film treatment: subjecting the base film obtained in step S2 to UV light radiation cyclization and cross-linking treatment;

[0020] S4: Post-processing: The treated base film obtained in step S3 is heat-set and then rolled up to obtain the composite film.

[0021] Further: in the step S1, the viscosity of the aromatic polyamide slurry is 30W-300W mPa.s, the solid content is 15%-30%, and the logarithmic viscosity is 2.2-3.0 dl / g. The solid content of the polyacrylonitrile slurry is 15%-25%;

[0022] Further: the mixing method is: dispersed mixing and heated stirring, the heating temperature is 50°C-100°C; after mixing, the mixed polymer slurry has a solid content of 15%-25% and a viscosity of 20W-100W mPa.s;

[0023] Further: in step S1, the solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and triethyl phosphate.

[0024] Further: in step S2, after the slurry is discharged, it passes through two liquid solvent baths, and the components of the liquid solvent baths are organic solvent and water; the organic solvent is preferably the same as the first solvent or the second solvent in step S1. Preferably, in the first liquid solvent bath and the second liquid solvent bath, the mass ratio of the organic solvent to water is different;

[0025] More preferably, in the first liquid solvent bath, the mass ratio of the organic solvent to water is 6:4-8:2;

[0026] More preferably, in the second liquid solvent bath, the mass ratio of the organic solvent to water is 3:7-7:3;

[0027] Further: in step S2, the mass fraction of water in the first liquid solvent bath is 5%-15% lower than the mass fraction of water in the second liquid solvent bath.

[0028] Further: in step S2, in the stretching process, the stretching ratio in the TD direction is 1.5-3.0 times.

[0029] Further: in step S2, the solvent of the cleaning step is pure water, the temperature is 20°C-70°C, and the total cleaning time is 2min-8min.

[0030] Further: in step S4, the composite film is fixed on both sides in the TD direction during the heat setting, the heat setting temperature is 250° C.-300° C., and the time is 0.5-3 min.

[0031] Further: in step S2, the drying temperature is 70°C-150°C, and the drying time is 1min-3min;

[0032] Further: in step S3, during the UV light radiation cyclization cross-linking treatment, a UV mixed light source is used to uniformly irradiate the upper and lower surfaces of the film with an irradiance of 3-50 mW / cm 2 , temperature is 70℃-150℃, and light radiation time is 3-30min.

[0033] Compared with the related art, the present invention has the following advantages:

[0034] In the composite membrane of the present invention, the raw materials interact with each other to improve the tensile strength and elongation of the composite membrane, which can not only improve the conductivity but also have better tensile properties in the process, is not easy to break, and can achieve a larger stretching ratio; due to the larger elongation at break, when used in the lamination, winding and other processes at the downstream lithium battery manufacturing end, its performance and yield are greatly improved; due to its excellent wettability and moisture retention rate, after the composite membrane is used as a diaphragm material to make a lithium battery, its performance in terms of cycle performance is significantly better than that of ordinary commercial diaphragms.

[0035] More importantly, the present application uses two kinds of raw materials in combination, and also uses liquid solvent to process the slurry in liquid state, and especially cooperates with ultraviolet radiation treatment, and its overall effect is very outstanding, not only improving the tensile modulus of the composite film, avoiding the problem that the single material aromatic polyamide film is easy to break, so that the tensile strength and elongation of the composite film are significantly improved, and at the same time, the polyacrylonitrile cyclization cross-linking also improves the heat resistance of the composite film. When a larger stretching ratio is used for horizontal drawing, due to the filling of polyacrylonitrile, the three-dimensional space of aromatic polyamide is not easily compressed. As a diaphragm in the manufactured lithium battery, polyacrylonitrile swells under the action of the electrolyte, making the three-dimensional structure formed in the composite film more three-dimensional, thereby effectively increasing the transmission efficiency of ions, thereby improving the ionic conductivity, improving the charge and discharge rate of the battery, effectively reducing the addition amount of lithium battery electrolyte and significantly improving the cycle performance of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is an electron microscope image of the surface of a composite membrane for a lithium battery provided in one embodiment of the present invention.

[0037] Figure 2 A schematic diagram of an exemplary structure of polyacrylonitrile containing free radicals after being irradiated with ultraviolet light provided in one embodiment of the present invention.

[0038] Figure 3 An exemplary structural diagram of local cyclization and cross-linking of polyacrylonitrile provided in one embodiment of the present invention.

[0039] Figure 4 An exemplary structural diagram of the interaction between polyacrylonitrile and aromatic polyamide provided in one embodiment of the present invention. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below. However, it should be understood that the description herein is only used to explain the present invention and is not used to limit the scope of the present invention.

[0041] Unless otherwise defined, all technical terms and scientific terms used herein have the same meanings as those generally understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The characterization means involved in this article can refer to the relevant descriptions in the prior art and will not be repeated herein.

[0042] Terminology Note:

[0043] The "molecular weight" used in this article is the viscosity-average molecular weight. The viscosity-average molecular weight (Viscosity-average Molecular Weight), whose full name is viscosity average molecular weight, is the molecular weight of a polymer measured by a dilute solution viscosity method.

[0044] Aromatic polyamide, also known as aramid fiber.

[0045] Poly(p-phenylene terephthalamide), also known as para-aramid (poly-p-phenyleneterephthamide, PPTA).

[0046] Poly(m-phenylene isophthalamide), also known as meta-aramid (PMIA).

[0047] Tensile strength: It is the maximum stress value that a material can withstand before it breaks.

[0048] Tensile strength MD: Transverse index of tensile strength (Machine Direction).

[0049] Tensile strength TD: Transverse Direction of tensile strength.

[0050] Elongation: Elongation refers to the percentage of the total deformation ΔL of the gauge section after the specimen is tensile fractured to the original gauge length L.

[0051] Elongation MD: Elongation in the transverse direction (Machine Direction).

[0052] Elongation TD: Elongation in the longitudinal direction (Transverse Direction).

[0053] MD direction: transverse (Machine Direction).

[0054] TD direction: Transverse Direction.

[0055] Linear thermal shrinkage: Linear shrinkage refers to the ratio of the change in the length direction of the material during temperature changes to the original length.

[0056] The raw materials of the lithium battery composite membrane of the present invention are polyacrylonitrile and aromatic polyamide. The mass ratio of the two is: 1: (1-20), for example: 1: 1, 1: 3, 1: 5, 1: 7, 1: 9, 1: 10, 1: 12, 1: 14, 1: 16, 1: 18, 1: 20, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. By adjusting the preferred blending ratio of aromatic polyamide and polyacrylonitrile, the prepared composite membrane not only has excellent mechanical properties, but also can reduce the amount of electrolyte used and improve the cycle performance of the battery when it is made into a diaphragm for use in the battery.

[0057] As a further preferred embodiment, the molecular weight of the polyacrylonitrile is 30W-50W, for example 30W, 32W, 34W, 36W, 38W, 40W, 42W, 44W, 46W, 48W, 50W. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] The aromatic polyamide described in the present invention includes: poly(p-phenylene terephthalamide) (PPTA / para-aramid), poly(m-phenylene isophthalamide) (PMIA / meta-aramid), heterocyclic aromatic polyamide containing heteroatoms, wholly aromatic polyamide of ortho-aramid, etc.; preferably PPTA or PMIA.

[0059] Most preferably, the aromatic polyamide is selected from PMIA. Poly(m-phenylene isophthalamide) (PMIA) is a polymer with meta-phenylene isophthalamide bonds on the backbone chain, and a strong hydrogen bond network structure is formed between its molecular chains. The above microstructure makes it have excellent heat resistance, flame retardancy, chemical stability and mechanical properties on a macro scale.

[0060] Preferably, the aromatic polyamide uses aromatic polyamide resin or aromatic polyamide fiber.

[0061] The base film made of single polymer aromatic polyamide material usually has some performance defects, such as poor tensile properties, easy breakage and tearing during the production process, and insufficient elongation. Polymer blending extrusion can effectively combine the advantages of aromatic polyamide and polyacrylonitrile (PAN), and improve the mechanical properties of the base film while maintaining high porosity, heat resistance and good electrical properties.

[0062] The molecular weight of the aromatic polyamide is 9W-35W, such as 9W, 10W, 15W, 20W, 25W, 30W, 35W, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] As a further preferred embodiment, the linear heat shrinkage of the composite film is: at 250°C, the heat shrinkage in the MD direction and the TD direction is 0-2%, for example 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, etc. The present invention is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. A diaphragm with a large linear heat shrinkage is prone to shrinkage in a high temperature environment, resulting in a reduction in the area of ​​the electrode covered by the diaphragm, resulting in a loss of the barrier of the diaphragm between the electrodes, causing a short circuit, thereby affecting the capacity and cycle performance of the battery. The present invention controls the heat shrinkage of the composite film in the above range very well, avoiding the occurrence of the above problems.

[0064] The tensile strength MD of the composite film is 85-160Mpa, such as 85Mpa, 90Mpa, 100Mpa, 110Mpa, 120Mpa, 130Mpa, 140Mpa, 160Mpa, etc. The present invention is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The tensile strength TD of the composite film is 65-130Mpa, such as 65Mpa, 70Mpa, 80Mpa, 90Mpa, 100Mpa, 110Mpa, 120Mpa, 130Mpa, etc. The present invention is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0065] The elongation MD of the composite film is 150%-350%, and the elongation TD is 150%-350%, for example, 150%, 160%, 170%, 180%, 190%, 200%, 210%, 220%, 230%, 240%, 250%, 260%, 270%, 280%, 290%, 300%, 310%, 320%, 330%, 340%, 350%, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0066] The liquid absorption rate of the composite film is 150% to 200%, for example, 150%, 160%, 170%, 180%, 190%, 200%, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] As a further preferred embodiment, the thickness of the composite film is generally 8-50 μm, such as 8 μm, 9 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc. The present invention is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Of course, if necessary, a thickness outside the range is also acceptable.

[0068] The air permeability of the composite film is 50-300s / 100ml, for example, 50s / 100ml, 100s / 100ml, 150s / 100ml, 200s / 100ml, 250s / 100ml, 300s / 100ml, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] The porosity of the composite membrane is 50%-80%, such as 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc. The present invention is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. By increasing the porosity of the composite membrane, ion transmission is facilitated and electrical conductivity is improved.

[0070] As a further preferred embodiment, the composite membrane is made of aromatic polyamide and polyacrylonitrile, and the polyacrylonitrile is partially cyclized and cross-linked by UV light radiation treatment, and the positively charged amide groups of the aromatic polyamide are attracted to each other to form a chain-shaped winding structure. The irradiance is 3-50mW / cm 2 , temperature is 70℃-150℃, and light radiation time is 3-30min.

[0071] Specifically, upon ultraviolet radiation, the polyacrylonitrile structure generates alkyl radicals and / or polyene radicals, which then react with oxygen in the air, and some of the radicals form structures containing oxygen radicals, for example, Figure 2 The structure shown, then the free radical will attack the C in the cyano group, and finally undergo a cyclization reaction to form a partially cyclized cross-linked structure, for example, Figure 3 Then, they combine with the hydrogen bonds of aromatic polyamide to form a chain-like winding structure, for example, Figure 4 The structure shown is the composite membrane structure described in the present application. The structure has an excellent effect through the synergistic effect between the two raw materials and the specific ultraviolet radiation.

[0072] The method for preparing the composite film for lithium battery comprises the following steps:

[0073] S1: slurry preparation: dissolving aromatic polyamide in a first solvent to obtain aromatic polyamide slurry, dissolving polyacrylonitrile in a second solvent to obtain polyacrylonitrile slurry, and mixing the two evenly to obtain a mixed polymer slurry;

[0074] S2: Film making: Extruding the mixed polymer slurry through an extrusion die and subjecting it to liquid solvent treatment, stretching, washing, and drying to obtain a base film;

[0075] S3: base film treatment: subjecting the base film obtained in step S2 to UV light radiation cyclization and cross-linking treatment;

[0076] S4: Post-processing: The treated base film obtained in step S3 is heat-set and then rolled up to obtain the composite film.

[0077] As a further preferred embodiment, the viscosity of the aromatic polyamide slurry is 30W-300W mPa.s, such as 30W mPa.s, 40W mPa.s, 50W mPa.s, 70W mPa.s, 90W mPa.s, 110W mPa.s, 130W mPa.s, 150W mPa.s, 170W mPa.s, 190W mPa.s, 210W mPa.s, 230W mPa.s, 250W mPa.s, 270W mPa.s, 290W mPa.s, 300W mPa.s, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. The use of high viscosity or extra-high viscosity (30W-300W mPa.s) aromatic polyamides such as polyisophthalamide (meta-aramid) has the effect of increasing the strength of the base film and improving the stability of the film.

[0078] The solid content of the aromatic polyamide slurry is 15%-30%, for example 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0079] The aromatic polyamide slurry has a logarithmic viscosity of 2.2-3.0 dl / g, for example, 2.2 dl / g, 2.3 dl / g, 2.4 dl / g, 2.5 dl / g, 2.6 dl / g, 2.7 dl / g, 2.8 dl / g, 2.9 dl / g, and 3.0 dl / g. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0080] The calculation formula of the inherent viscosity is:

[0081] {η}=(lnηr) / c (Formula 1)

[0082] Where ηr is the relative viscosity (also known as viscosity ratio), which is the ratio of the viscosity (η) of the polymer solution (or dispersed phase) to the viscosity (η0) of the pure solvent (or continuous phase); c is the concentration of the solution.

[0083] As a further preferred embodiment, the solid content of the polyacrylonitrile slurry is 15%-25%, for example 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0084] The solid content of the mixed polymer slurry is 15%-25%, for example 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0085] The viscosity of the mixed polymer slurry is 20W-100W mPa.s, for example, 20W mPa.s, 30W mPa.s, 40W mPa.s, 50W mPa.s, 60W mPa.s, 70W mPa.s, 80W mPa.s, 90W mPa.s, 100W mPa.s, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0086] As a further preferred embodiment, in step S1, the mixing method is: dispersed mixing and heated stirring, and the stirring temperature is 50°C-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0087] As a further preferred embodiment, the first solvent and the second solvent of the present invention are selected from one or more of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and triethyl phosphate.

[0088] Dimethylacetamide (DMAC or DMA), full name N,N-dimethylacetamide, chemical formula CH3C(O)N(CH3)2, commonly used as a non-protonic polar solvent, colorless transparent liquid. Dimethylformamide (DMF), full name N,N-dimethylformamide, is an organic compound, chemical formula C3H7NO, a colorless transparent liquid. Dimethyl sulfoxide (DMSO) is a sulfur-containing organic compound, chemical formula C2H6OS, colorless, odorless, transparent liquid at room temperature, a hygroscopic flammable liquid. Methylpyrrolidone (N-Methylpyrrolidone, NMP), full name N-methylpyrrolidone, chemical formula C5H9NO, a colorless to pale yellow transparent liquid. Triethyl phosphate (TEP) is a colorless transparent liquid with a melting point of -56.5°C, a boiling point of 215-216°C, and a relative density (20°C) of 1.0695. It is completely soluble in water and easily soluble in organic solvents such as ethanol and etherbenzene.

[0089] As a further preferred embodiment, in step S2, the solvent used for the liquid solvent treatment is the same as the solvent in step S1. The liquid solvent treatment is preferably carried out twice, i.e., including the first liquid solvent treatment and the second liquid solvent treatment. In the first liquid solvent treatment, the mass ratio of the organic solvent to water is 6:4-8:2, for example, 6:4, 7:3, 8:2, etc. In the second liquid solvent treatment, the mass ratio of the organic solvent to water is 3:7-7:3; for example, 3:7, 4:6, 5:5, 6:4, 7:3, etc. The foregoing is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0090] Specifically, the mass fraction of water in the first liquid solvent treatment is 5%-15% lower than the mass fraction of water in the second liquid solvent treatment, for example 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0091] The solvent used in the liquid solvent treatment is the same as the first solvent or the second solvent (the solvent for dissolving aromatic polyamide and the solvent for dissolving acrylonitrile) in step S1. For example, the above solvents are both N,N-dimethylacetamide (DMAC), and the organic solvent used in the liquid solvent treatment is also N,N-dimethylacetamide, which is used to achieve non-solvent induced phase separation of the two components of aromatic polyamide and polyacrylonitrile during the liquid solvent treatment. The present invention is not limited to the single solvent exemplified above, and the solvent used in the liquid solvent treatment and the solvent in step S1 can also be selected as a mixed solvent of two or more, as long as the solvent used in the liquid solvent treatment is the same as that used in step S1.

[0092] The principle of liquid solvent treatment is to use non-solvent induced phase separation to make the two components of uncrosslinked aromatic polyamide and polyacrylonitrile in the extruded slurry undergo phase separation and solidification at the same time. The mass ratio of the organic solvent to water in the first liquid solvent treatment is set to be different from the mass ratio of the organic solvent to water in the second liquid solvent treatment, which is used to adjust the pore size and porosity of the base membrane. Among them, when the mass fraction of water in the first liquid solvent treatment is 5%-15% lower than the mass fraction of water in the second liquid solvent treatment, the effect of adjusting the pore size and porosity of the base membrane is the best. Too low or too high may have a more obvious impact.

[0093] As a further preferred embodiment, in step S2, the stretching ratio in the TD direction is 1.5-3.0 times; for example, 1.5 times, 1.6 times, 1.7 times, 1.8 times, 1.9 times, 2.0 times, 2.1 times, 2.2 times, 2.3 times, 2.4 times, 2.5 times, 2.6 times, 2.7 times, 2.8 times, 2.9 times, 3.0 times, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0094] Ordinary aromatic polyamide-based membranes are prone to breakage under large stretching ratios, and the three-dimensional space gap is easily reduced, resulting in a decrease in air permeability, which directly reduces the ion conductivity of the membrane in lithium-ion batteries.

[0095] The composite film preparation method provided by the present invention significantly enhances the tensile strength and elongation of the composite film. Due to the filling of polyacrylonitrile, the three-dimensional space of the aromatic polyamide is not easily compressed when a large stretching ratio is used for horizontal stretching, and in the subsequent lithium battery manufactured, the polyacrylonitrile swells under the action of the electrolyte, making its three-dimensional structure more three-dimensional, which can effectively increase the transmission efficiency of ions.

[0096] As a further preferred embodiment, in step S2, the cleaning solvent is pure water, the cleaning temperature is 20°C-70°C; the total cleaning time is 2min-8min;

[0097] The cleaning temperature is 20°C-70°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0098] The total cleaning time is controlled at 2 min-8 min, for example, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, etc. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0099] The function of the cleaning is as follows: in the above steps, the membrane treated with the liquid solvent has not completely phase-separated, and the cleaning enables the phase separation to be completed completely and removes the solvent at the same time.

[0100] As a further preferred embodiment, in step S4, the two sides of the composite film in the TD direction are fixed during the heat setting, the heat setting temperature is 250°C-300°C, for example, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, etc., and the time is 0.5-3min, for example, 0.5min, 1min, 1.5min, 2min, 2.5min, 3min, etc.

[0101] As a further preferred embodiment, the drying temperature is 70°C-150°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc., and the drying time is 1min-3min, for example, 1min, 1.5min, 2min, 2.5min, 3min, etc.;

[0102] As a further preferred embodiment, in the UV light radiation cyclization cross-linking treatment, a UV mixed light source is used to uniformly irradiate the upper and lower surfaces of the film with an irradiance of 3-50 mW / cm 2 , temperature is 70-150℃, and light radiation time is 3-30min.

[0103] Irradiance: 3-50mW / cm 2 , for example 3mW / cm 2 , 5mW / cm 2 , 7mW / cm 2 , 9mW / cm 2 、10mW / cm 2 、15mW / cm 2 , 20mW / cm 2, 25mW / cm 2 、30mW / cm 2 、35mW / cm 2 , 40mW / cm 2 , 45mW / cm 2 、50mW / cm 2 The temperature is 70-150°C, such as 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc. The light irradiation time is 3-30min, such as 3min, 4min, 5min, 10min, 15min, 20min, 25min, 30min, etc. The present invention is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0104] The main purpose of drying is to dry the moisture and a small amount of solvent on the film. The main function of UV mixed light source radiation is to generate free radicals in polyacrylonitrile (PAN) to form cyclization and cross-linking and interact with aromatic polyamide.

[0105] Mixed light sources are more effective than single light sources, and commonly used UV radiation mixed light sources can be used.

[0106] The above-mentioned temperature and time are selected because different drying temperatures, irradiances and light irradiation times result in different degrees of cyclization and cross-linking. In principle, the higher the temperature, the irradiance of the UV mixed light source, and the longer the light irradiation time, the higher the degree of cyclization and cross-linking. However, the higher the temperature and the irradiance of the UV mixed light source and the longer the light irradiation time, the more they will affect the aromatic polyamide. Therefore, considering the above-mentioned factors, in order to obtain the best performance of the base film, the above-mentioned drying temperature range, UV irradiance, and light radiation time range are selected to obtain a base film with the best performance.

[0107] The heat-set base film can be rolled up to obtain a composite film for lithium batteries.

[0108] When the composite membrane for lithium battery of the present invention is used to make a diaphragm, it can be made directly into a diaphragm or by using common diaphragm manufacturing and processing processes such as coating. Preferably, the lithium battery includes: lithium metal battery, secondary button battery and power battery.

[0109] The preparation method of the composite membrane for lithium battery provided by the present invention is that after the aromatic polyamide slurry and the polyacrylonitrile slurry are mixed and extruded, under the action of the molecular force of the polyacrylonitrile, most of the pores of the aromatic polyamide are coated by the polyacrylonitrile, and then part of the polyacrylonitrile is cyclized and cross-linked by UV light curing, thereby improving the tensile modulus of the composite membrane, avoiding the problem that the single material aromatic polyamide membrane is easy to break, and the tensile strength and elongation of the composite membrane are significantly improved. At the same time, the polyacrylonitrile cyclization and cross-linking also improve the heat resistance of the composite membrane. When a larger stretching ratio is used for horizontal stretching, due to the filling of polyacrylonitrile, the three-dimensional space of the aromatic polyamide is not easily compressed. As a diaphragm in the manufactured lithium battery, the polyacrylonitrile swells under the action of the electrolyte, making the three-dimensional structure formed in the composite membrane more three-dimensional, thereby effectively increasing the transmission efficiency of ions, thereby improving the ion conductivity, improving the charge and discharge rate of the battery, effectively reducing the amount of lithium battery electrolyte added and significantly improving the cycle performance of the lithium battery. Furthermore, the composite membrane of the present application has a relatively high porosity and maintains a suitable air permeability, which is beneficial to gas diffusion and thus reduces local pressure accumulation, thereby improving the safety of the battery.

[0110] In order to further understand the present invention, the present invention is further described in detail below in conjunction with the best embodiment.

[0111] Example 1: (The mass ratio of polyisophthalamide to polyacrylonitrile in the membrane is 9:1)

[0112] 1320 g of N, N-dimethylacetamide (hereinafter referred to as DMAC) was added to the A reactor. The stirring speed of the reactor was 80 rpm, the temperature was controlled at 60 ° C, and 330 g of polyacrylonitrile powder with a molecular weight of 50W was slowly added and stirred for 4 hours. The actual end time point was when all the polyacrylonitrile was dissolved without any residue, and 1650 g of polyacrylonitrile (PAN) slurry was obtained.

[0113] Take 15kg of poly(m-phenylene isophthalamide) slurry, the solvent of which is DMAC, which is made from poly(m-phenylene isophthalamide) with a molecular weight of 11.2W, the inherent viscosity of the slurry is 2.64dl / g, the solid content is 16.5%, and the viscosity is 94W mPa.s, and add the slurry to the reactor. The stirring speed of the reactor is 120rpm, and the temperature is controlled at 70℃. Then slowly add 1375g of PAN slurry to the reactor, stir for 8h, and then degas.

[0114] The mixed slurry after vacuum degassing is injected into the first liquid solvent tank through an extrusion die to form a continuous soft film, and then immersed in the second liquid solvent tank for further solidification. The components in the first and second liquid solvent tanks are both DMAC and H2O mixed solutions, in which the mass proportion of DMAC (DMAC mass / mixed solution mass) is 70% and 60% respectively, the transmission speed is 5m / min, and then stretched at room temperature by a horizontal stretching machine at 2.0 times, and finally washed with a water tank.

[0115] Use oven drying, the oven temperature is set to 80℃, the drying time is 3min, and the film surface is evenly irradiated with UV mixed light source. The distance from the light source to the film is controlled at 50mm, and the irradiance is 3mW / cm 2 , the temperature is 150℃, and the light radiation time is controlled at 10min.

[0116] The final heat setting temperature was 270°C for 3 min. The film thickness was controlled at 15±1 μm by adjusting the feed rate. The test data of the finished coil is shown in Table 1.

[0117] Example 2 (the mass ratio of polyisophthalamide to polyacrylonitrile in the membrane is 7:3)

[0118] 5088g of N,N-dimethylacetamide (hereinafter referred to as DMAC) solution was added to a 10L reactor. The stirring speed of the reactor was 80rpm and the temperature was controlled at 60°C. 1272g of polyacrylonitrile powder with a molecular weight of 50W was slowly added and stirred for 4h. The actual end time point was when all the polyacrylonitrile was dissolved without any residue, and 6360g of polyacrylonitrile slurry was obtained.

[0119] Take 15kg of poly(m-phenylene isophthalamide) slurry, the solvent of which is DMAC, the molecular weight of poly(m-phenylene isophthalamide) is 11.2W, the logarithmic viscosity of the slurry is 2.64dl / g, the solid content is 16.5%, and the viscosity is 94W mPa.s, and add it to a 50L reactor. The stirring speed of the reactor is 120rpm, and the temperature is controlled at 70°C. Then slowly add 5303.6g of polyacrylonitrile slurry to the reactor, stop stirring after 8h, and then evacuate the reactor by vacuuming, the vacuum degree is -0.09MPa, turn off the vacuum pump, and let it stand for 8h.

[0120] The mixed slurry after vacuum degassing is extruded through a melt pump, a filter and a die head, and passes through a first liquid solvent tank and a second liquid solvent tank. The components in the first and second liquid solvent tanks are mixed solutions of DMAC and H2O, wherein the mass proportion of DMAC (DMAC mass / solution mass) is 70% and 60% respectively, and the transmission speed is 5m / min. It is then stretched at room temperature by a 2.0 times horizontal stretching machine, and then washed in 3 water tanks, the first 2 water tanks are at room temperature, and the temperature of the last water tank is controlled at 50°C.

[0121] The oven temperature was set at 80°C, the drying time was 1 min, and a UV mixed light source was used to irradiate the film surface evenly. The distance from the light source to the film was controlled at 50 mm, and the irradiance was 10 mW / cm 2 , the temperature is 70℃, and the light radiation time is controlled at 10min.

[0122] The final heat setting temperature was 270°C for 3 min. The film thickness was controlled at 15±1 μm by adjusting the feed rate. The test data of the finished coil is shown in Table 1.

[0123] Embodiment 3:

[0124] The operation steps are consistent with those of Example 1, except that the molecular weight of the selected poly(m-phenylene isophthalamide) is 9.2W, the inherent viscosity of the slurry is 2.2 dl / g, the solid content is 16.5%, and the viscosity is 34WmPa.s. When preparing the mixed polymer slurry, the stirring time is 6 hours.

[0125] The test data of the harvested coils are shown in Table 1.

[0126] Embodiment 4:

[0127] The operation steps are consistent with those in Example 1, except that the molecular weight of the selected polyacrylonitrile is 30W.

[0128] The test data of the harvested coils are shown in Table 1.

[0129] Embodiment 5:

[0130] The operation steps are the same as those in Example 1, except that the irradiance of the UV mixed light source is 30 mW / cm 2 The radiation time is 5 minutes and the temperature is 100℃.

[0131] The test data of the harvested coils are shown in Table 1.

[0132] Embodiment 6:

[0133] The operation steps are consistent with those in Example 1, except that the mass proportion of N,N-dimethylacetamide in the first liquid solvent tank is 65%, and the mass proportion of N,N-dimethylacetamide in the second liquid solvent tank is 55%;

[0134] The test data of the harvested coils are shown in Table 1.

[0135] Comparative Example 1:

[0136] The operation steps are consistent with those in Example 1, except that there is only a single component poly(m-phenylene isophthalamide) slurry in the reactor without polyacrylonitrile, and there is no UV light radiation and heating step in the subsequent process steps.

[0137] The test data of the harvested coils are shown in Table 1.

[0138] Comparative Example 2:

[0139] The operation steps were the same as those in Example 1, except that the raw material was only polyacrylonitrile. The film prepared in this way shrank violently and broke during the drying step, and could not be made into a film.

[0140] Comparative Example 3:

[0141] When the mass ratio of polyacrylonitrile in the mixed slurry exceeds 50%, the viscosity of the slurry drops sharply to 9W mPa.s. After being extruded from the die head and entered into the liquid solvent tank, it was found that the slurry had serious floating phenomenon and could not form a film continuously.

[0142] Comparative Example 4:

[0143] A commercial PE-coated 14 μm separator was used.

[0144] The test data of the coil is shown in Table 1.

[0145] Comparative Example 5:

[0146] The operation steps are the same as those in Example 1, except that there is no UV light radiation treatment on the film surface.

[0147] Effect Example 1

[0148] The composite films prepared in the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 5 were tested for their basic data, i.e., the linear heat shrinkage in the TD and MD directions, the elongation in the TD and MD directions, the tensile strength in the TD and MD directions, the liquid absorption rate, the thickness, the porosity, and the air permeability. The test methods of these parameters are all conventional test methods. The basic data of the composite film test are shown in Table 1. As can be seen from Table 1, compared with the single material aromatic polyamide base film of Comparative Example 1, the composite film provided by the present invention has significantly improved air permeability, tensile strength, and elongation. Comparing Example 1 with Example 2, it is found that when the mass ratio of polyisophthalamide to polyacrylonitrile is relatively high, the tensile strength of the base film is relatively high. By comparing Example 1 and Example 6, it is found that when the solvent content of the liquid solvent tank of Example 6 is selected, the air permeability and tensile strength of the base film are improved, but at the same time the elongation is slightly decreased. The improvement in the air permeability of Example 6 is due to the fact that the higher the concentration of N,N-dimethylacetamide, the slower the phase conversion rate, the more sponge-like pores are formed, the smaller the corresponding air permeability, and the higher the corresponding porosity. The concentration of N,N-dimethylacetamide in Example 6 is lower than that in Example 1, so the air permeability is improved, while the porosity is reduced.

[0149] In combination with the embodiments of the present invention and the comparative examples, it is found that the comparative examples cannot simultaneously improve the tensile strength / elongation of the composite film and ensure a low thermal shrinkage rate, while embodiments 1-6 of the present invention achieve simultaneous improvement in the above two aspects. In combination with embodiments 1-6 of the present invention and comparative example 1, it is found that in comparative example 1, the tensile strength and elongation are both low when the porosity is increased, while embodiments 1-6 of the present invention significantly improve the tensile strength and elongation while having high porosity and high thermal stability. In summary, the present invention has significant technical innovation and has realistic technical effects in the industry.

[0150] Table 1 Basic data test results

[0151]

[0152] Effect Example 2

[0153] The membrane samples of Example 1, Comparative Example 1 and Comparative Example 5 were immersed in the second liquid solvent tank for 1 hour, and after being fully immersed, they were taken out for manual stretching test. The difference in mechanical properties of the two membranes was observed through stretching. The membrane of Example 1 had resilience after being immersed and stretched in any direction, while the membranes of Comparative Examples 1 and Comparative Examples 5 would be permanently deformed after being immersed and stretched.

[0154] Since a diaphragm could not be prepared in Comparative Example 2, a sample of the membrane after passing through the second liquid solvent tank step during the membrane preparation process was taken and a tensile test was performed in the same manner as above. It was observed that the membrane had poor ductility and was easily broken.

[0155] Through the above experiments, it can be found that the diaphragm of Example 1 of the present invention has a new characteristic, namely, the rebound resilience generated after being soaked in an organic solution, while the raw material components of the membrane do not have this characteristic. Therefore, the rebound resilience comes from the membrane treatment method of the present invention.

[0156] There are already public data studies on the reaction of cyclization and cross-linking of polyacrylonitrile by UV light radiation treatment. In the present invention, aromatic polyamide and polyacrylonitrile are mixed, and then UV light radiation is used to promote local cyclization and cross-linking of polyacrylonitrile in the mixture. The cyano group in the cross-linked product is combined with the amide group of the aromatic polyamide by hydrogen bonding to form an intertwined structure. After the diaphragm of the present invention is swollen by solvent, it exhibits rubber-like resilience due to the internal cross-linked structure. This property can be applied to batteries to reduce the adverse effects of volume expansion of battery materials during charging and discharging.

[0157] Effect Example 3 (Secondary Button Battery Performance Comparison Experiment):

[0158] Experimental methods:

[0159] Preparation of secondary button cells: Selection The lithium metal is used as the negative electrode, and the positive electrode material is the 811 series ternary material. After homogenization, coating, baking, and rolling, a special sampler is used to punch samples (with a diameter of 13mm). The diameter of the diaphragm sample is 19mm. The electrolyte is the commercial Shanshan 013 model ternary series. The 2032 model button battery is assembled in a glove box filled with argon (O2<0.01ppm, H2O<0.01ppm).

[0160] The diaphragm samples were respectively taken using the composite membrane for lithium batteries provided by the present invention and a commercial diaphragm (Celgard), wherein the commercial diaphragm was an 8 μm coated polyethylene (PE) ceramic membrane.

[0161] Secondary battery performance test: The manufactured CR2032 model is charged, left to stand for 24 hours, and then placed on a blue electric test cabinet, and charged at 0.2C to a voltage of 4.25V, and then charged at a constant voltage to a current rate of ≤0.05C, and left to stand for ≥10 minutes, and then discharged at 0.2C to a voltage of 2.5V, and then left to stand for ≥10 minutes. This step is a charge-off cycle. The changes in the number of cycles and the discharge specific capacity value are recorded, and the results are shown in Table 2. It can be seen from Table 2 that compared with commercial diaphragms, the composite membrane provided by the present invention has significantly improved the capacity and capacity retention rate of the secondary battery after 100 cycles, proving that the performance of the composite membrane provided by the present invention is significantly better than that of commercial diaphragms.

[0162] Table 2 Test results

[0163]

[0164] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite membrane for lithium batteries, characterized in that: The raw materials of the composite membrane include aromatic polyamide and polyacrylonitrile, and the mass of the polyacrylonitrile does not exceed the mass of the aromatic polyamide.

2. The composite membrane according to claim 1, characterized in that: In the composite membrane, the polyacrylonitrile is a partially cyclized and mutually cross-linked structure, which interacts with the aromatic polyamide to form a chain-shaped entangled structure, namely the composite membrane; Preferably, the mass ratio of the aromatic polyamide to polyacrylonitrile is: (1-20):1; The aromatic polyamide is poly(p-phenylene terephthalamide), poly(m-phenylene isophthalamide), heterocyclic aromatic polyamide containing heteroatoms or fully aromatic polyamide of ortho-aramid, and has a molecular weight of 9W-35W; The molecular weight of the polyacrylonitrile is 30W-50W.

3. The composite membrane according to claim 2, characterized in that: The composite membrane is made by mixing aromatic polyamide and polyacrylonitrile; Preferably, after the two raw materials are mixed together, the mixture is treated with a liquid solvent and stretched; Preferably, the aromatic polyamide and polyacrylonitrile are treated by UV light radiation, preferably after the liquid solvent treatment, the liquid solvent treated product is subjected to UV light radiation treatment on both sides.

4. The composite membrane according to claim 2 or 3, characterized in that: Before the two raw materials are blended, solvents are added to prepare aromatic polyamide slurry and polyacrylonitrile slurry respectively; The liquid solvent is a mixed solvent of an organic solvent and water; the organic solvent here is preferably the same as the solvent used to prepare the slurry; Preferably, the solid content of the aromatic polyamide slurry is 15%-30%; the solid content of the polyacrylonitrile slurry is 15%-25%; more preferably, the solid content of the mixed polymer slurry is 15%-25%.

5. The composite membrane according to claim 1, characterized in that: The composite film meets at least one of the following four parameters, preferably meets the following four parameters at the same time: Linear heat shrinkage: 0-2% in both MD and TD directions; Elongation: 150%-350% in both MD and TD directions; Tensile strength: 65Mpa to 160Mpa in both MD and TD directions. Preferably, the tensile strength in MD direction is higher than that in TD direction. Liquid absorption rate: 150%~200%.

6. A method for preparing the composite film for lithium battery, characterized in that: The following steps are involved: S1: slurry preparation: dissolving aromatic polyamide in a first solvent to obtain aromatic polyamide slurry, dissolving polyacrylonitrile in a second solvent to obtain polyacrylonitrile slurry, and mixing the two evenly to obtain a mixed polymer slurry; S2: Film making: discharging the mixed polymer slurry in a film form into a liquid solvent for treatment, and then stretching, washing, and drying to obtain a base film; S3: base film treatment: subjecting the base film obtained in step S2 to UV light radiation cyclization and cross-linking treatment; S4: Post-processing: The treated base film obtained in step S3 is heat-set to obtain the composite film.

7. The method according to claim 6, characterized in that: In step S1, the aromatic polyamide slurry has a viscosity of 30W-300W mPa.s, a solid content of 15%-30%, and a logarithmic viscosity of 2.2-3.0 dl / g; The solid content of the polyacrylonitrile slurry is 15%-25%; Preferably, the mixed polymer slurry has a solid content of 15%-25% and a viscosity of 20W-100W mPa.s; Preferably, the mixing method is: dispersed mixing and heated stirring, and the heating temperature is 50°C-100°C.

8. The method according to claim 6, characterized in that: In step S2, the slurry is treated with a liquid solvent twice after being discharged, and the components of the liquid solvent are an organic solvent and water; the organic solvent is preferably the same as the first solvent or the second solvent in step S1; and the mass ratio of the organic solvent to water is different in the first liquid solvent treatment and the second liquid solvent treatment; In the first liquid solvent treatment, the mass ratio of the organic solvent to water is 6:4-8:2; In the second liquid solvent treatment, the mass ratio of the organic solvent to water is 3:7-7:

3. Preferably, in step S2, the mass fraction of water in the first liquid solvent treatment is 5%-15% lower than the mass fraction of water in the second liquid solvent treatment.

9. The method according to claim 6, characterized in that: In step S2, in the stretching process, the stretching ratio in the TD direction is 1.5-3.0 times; In step S3, during the UV light radiation cyclization crosslinking treatment, a UV mixed light source is used to uniformly irradiate the upper and lower surfaces of the film with an irradiance of 3-50 mW / cm 2 , temperature is 70℃-150℃, and light radiation time is 3-30min.

10. The method according to claim 6, characterized in that: In step S1, the first solvent and the second solvent are independently selected from one or more of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and triethyl phosphate; preferably, the first solvent is the same as the second solvent; In step S2, the solvent of the cleaning step is pure water, the temperature is 20°C-70°C, and the total cleaning time is 2min-8min; Preferably, the drying temperature is 70°C-150°C and the drying time is 1min-3min; In step S4, the two sides of the composite film in the TD direction are fixed during the heat setting, and the heat setting temperature is 250° C.-300° C. and the time is 0.5-3 min.